The men who built America [videorecording (DVD)] - Magan, Ruán; Segaller, Adam Jonas; Rolland, Eric; Chmiel, Michael; Morck, Justin, 1983- (Lionsgate, 2013)
Vanderbilt, Rockefeller, Carmegie, Morgan, Ford, the Men Who Built America. Meet the titans who forged the foundation of modern America and created the American Dream. The mini-series shines a spotlight on the influential builders, dreamers and believers whose feats transformed the United States. a nation decaying from the inside after the Civil War, into the greatest economic and technological superpower the world had ever seen.